Pandangan Memakai Cadar Di Kampus Bagi Mahasiswi Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto - Salma, Abidah (Jurnal SUARGA: Studi Keberagamaan dan Keberagaman, 2024)
This study aims to explore the experiences and views of female students of the State Islamic University Professor Kiai Haji Saifuddin Zuhri Purwokerto in using the veil in the campus environment. Using a qualitative approach, this study involved in-depth interviews and participatory observation to understand the motivations, challenges, and adaptation strategies of female college students regarding the use of the veil. The results showed that female students have various motivations, ranging from religious commitment to self-protection, but also face challenges in social interactions and academic activities. The findings provide valuable insights for the development of inclusive and supportive campus policies for female students who wear the veil.